Improving the Character of Caring for the Environment for Tanjungrejo Village Children through Education on the Utilization of Plastic Waste and Planting Practices - Fauziah, Nurul; Sintya Yuliastuty, Devi (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2023)
The Character is something that is inherent in a person and is formed from his family environment from an early age. However, the character of each person is clearly different, this happens because of several factors, one of which is the environmental factor in which he lives. The background of this research is that there is a problem of character education which is still quite minimal among the children of the Tanjungrejo Village, especially regarding environmental awareness. This study aims to increase knowledge and insight about character education by educating the use of plastic waste into flower pots and planting plants for children in the Tanjungrejo Village. The type of research used is a qualitative descriptive approach, because researchers want to know and provide value-based experiences related to increasing the character of caring for the environment for Tanjungrejo Village Children through Education on the Utilization of Plastic Waste and Planting Practices. The target or target is the children in the Tajungrejo Village, which totals approximately 50 children. Sources of data obtained from field studies or primary data and secondary data obtained from relevant journals or articles. The results of the study show that the character of caring for the environment can be applied to children in the Tanjungrejo Village with Education on the Utilization of Plastic Waste and Planting Practices. The character of caring for the environment needs to be applied from an early age so that children grow into individuals who care about their environment, especially in the Tanjungrejo sub-district